Effect of Different Types of Smoking (Cegarette, hookah and vape) on Neuregulin-1 and Other Biochemical Parameters of Cardiac Health for Al-Mustansiriyah University Students Smoking ( cigarette, hookah and vape) on Heart Health for Mustansiriyah University Students - Hussain, Zaman; T.mohammed, Mostafa (University of Thi-Qar Journal of Science, 2024)
Tobacco smoking remains a significant contributor to preventable illness and premature mortality worldwide, posing a substantial risk factor for various cardiovascular diseases (CVDs). This study aimed to determine the impact of different smoking methods on cardiac function and oxidative stress parameters, focusing on cigarette smoking, hookah, and vape. A total of 120 male participants were splitted into four groups: healthy controls, cigarette smokers, hookah users, and vape users. Blood samples were collected and analyzed for oxidative stress markers, cardiac function indicators, and neuregulin-1 (NRG-1) levels, a peptide with cardioprotective potential. When compared to controls, the results showed that smokers had significantly higher concentrations of total oxidative stress (TOS) and lower concentrations of total antioxidant capacity (TAC), with hookah having the most noticeable impact. Both the hookah and cigarette groups had noticeably higher levels of neuregulin-1, suggesting possible heart stress. Moreover, smokers showed increased Creatine kinase-MB (CK-MB) levels and lactate dehydrogenase (LDH), which may indicate cardiac injury. The results of correlation analysis showed a strong relationship between LDH and NRG-1, indicating the possibility of using both of them together as markers of smoking-related cardiac risk. The diagnostic usefulness of TOS, TAC, Neuregulin-1, LDH, and CK-MB in differentiating smokers from non-smokers was shown by receiver operating characteristic (ROC) analysis; CK-MB showed the highest sensitivity and specificity. These results highlight how smoking hurts heart health, emphasizing the importance of comprehensive preventive strategies and smoking cessation interventions to mitigate the burden of CVDs associated with tobacco use.